2000
DOI: 10.1210/jc.85.8.2897
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Isoform A But Not B Is Expressed in Endometriosis

Abstract: We previously demonstrated that 17beta hydroxysteroid dehydrogenase type 2, the enzyme that inactivates estradiol to estrone, is expressed in luteal eutopic endometrium in response to progesterone but not in simultaneously biopsied peritoneal endometriotic tissue. This molecular evidence of progesterone resistance, together with the clinical observation of resistance of endometriosis to treatment with progestins, led us to determine the levels of progesterone receptor (PR) isoforms PR-A and PR-B in eutopic end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
284
1
13

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(322 citation statements)
references
References 37 publications
24
284
1
13
Order By: Relevance
“…At the tissue level, endometriosis may resist the antiproliferative effect of progesterone by the predominant expression of the inhibitory PR-A isoform instead of the stimulatory PR-B isoform (Attia et al 2000).…”
Section: Insensitivity To Anti-proliferative Signalsmentioning
confidence: 99%
“…At the tissue level, endometriosis may resist the antiproliferative effect of progesterone by the predominant expression of the inhibitory PR-A isoform instead of the stimulatory PR-B isoform (Attia et al 2000).…”
Section: Insensitivity To Anti-proliferative Signalsmentioning
confidence: 99%
“…The data on expression of PRs are also rather controversial: Misao et al (1999) have reported significantly higher levels of PRB mRNA in ovarian endometriosis samples compared to the normal endometrium. Attia et al (2000) have reported that PRB was not expressed in non-ovarian endometriosis, while Bukulmez et al (2008) detected three isoforms PRC, PRB and PRA in ovarian endometriomas. In contrast, our results showed no significant differences in mRNA levels of PRAB (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Показано, что ПР-A и ПР-B экспрессируются преимущественно в эутопическом эндометрии у больных эндометриозом, но у больных с наступившей беременностью уровень экспрессии не отличался от такового у больных с ненаступившей беременностью [10]. Дополнительно анализ эутопи-ческого эндометрия с использованием иммуноблот-тинга у больных эндометриозом показал равное ко-личественное присутствие ПР-A и ПР-B, преоблада-ющее в стромальных клетках [14].…”
Section: Discussionunclassified
“…Прогесте-рон вызывает децидуализацию эндометрия и готовит эндометрий для нидации эмбриона, проявляя дей-ствие через прогестероновый рецептор А и прогесте-роновый рецептор В (ПР-A, ПР-B соответственно), экспрессия обоих рецепторов выражена в эндоме-трии во всех фазах менструального цикла [33]. О раз-личиях в экспрессии ЭР и ПР и их изоформ в эуто-пическом эндометрии при эндометриозе сообща-лось ранее [10,11,30]. Кроме того, показано, что экспрессия ЭР-альфа и ПР-B в стромальных клетках эктопического эндометрия была снижена, возмож-но, за счет резистентности к прогестерону при эндо-метриозе [16].…”
unclassified